Differential response related to genotoxicity between eggplant (Solanum melanogena) skin aqueous extract and its main purified anthocyanin (delphinidin) in vivo - Azevedo, Luciana; Alves de Lima, Patricia L.; Gomes, Jose C.; Stringheta, Paulo C.; Ribeiro, Daniel A.; Salvadori, Daisy Maria Favero [UNESP] (Elsevier B.V., 2007)
Anthocyanins are the largest group of water-soluble pigments in the plant kingdom. A number of studies have demonstrated that anthocyanins present antioxidant capacity and show inhibitory effects on the growth of some cancer cells. Thus, the goal of this study was to evaluate both the antimutagenicity/antigenotoxicity and mutagenicity/genotoxicity of aqueous extract obtained from the Solanum melanogena, a possible novel source of anthocyanin, and its main purified anthocyanin extract (delphinidin), using the single cell (comet) assay and micronucleus test. Pretreatment with higher doses of the purified anthocyanin (10 and 20 mg/kg b.w.) led to a statistically significant reduction (p < 0.05) in the frequency of micronuclei in polychromatic erythrocytes induced by cyclophosphamide. The pattern of reduction ranged from 48% to 57% independent of concentration. No apparent: genotoxicity and mutagenicity was found for either the anthocyanin or delphinidin extracts. Taken together, these results suggest that mice pre-treated with specific compounds present in anthocyanins (delphinidin) displayed a lower incidence of mutations induced by cyclophosphamide. This finding emphasizes the potential of natural colorants to prevent mutations and also the applicability of genotoxic evaluation for improving health. Furthermore, the results presented here could be an additional argument to support the use of anthocyanins in the diet. (c) 2006 Published by Elsevier Ltd.
Keywords: anthocyanins; single cell gel (comet) assay; micronucleus test; mice; antimutagenesis